(untitled) (European Journal of Pure and Applied Mathematics, 2024)
Let A be a *-algebra with unit I and P_1 and P_2 = I - P_1 includes a non-trivial projections, and let λ C{0,-1}. In this paper, We aim to study the characterization of nonlinear mixed λ-Jordan triple derivation on *-algebras. As an application, we can also apply our results on prime *-algebras, factor von-Neumann algebras and standard operator algebras.